Iodine: Physiological importance and food sources. Issue 1 (12th February 2023) - Nedić, Olgica
Abstract: Iodine is essential for humans who can ingest or inhale different forms of this microelement. Its primary role is to be a constituent of thyroid hormones that control basal metabolism, growth, and development. Iodine deficiency causes major health problems and still persists in the population. During pregnancy, it may endanger neurodevelopment and even the life of the fetus. The objective of this article is to review the physiological importance of iodine, the consequences of iodine deficiency, methods to determine iodine status, recommendations for satisfactory iodine intake and risk limits, data on iodine concentrations in most common foods, as well as procedures that can increase iodine content in food. Iodization of kitchen salt is a method used for almost a century, but newer techniques for the production of iodine‐fortified foods have emerged offering additional means to deal with insufficient iodine intake. Biotechnology solutions for food fortification, which include iodine addition during and after plant/animal growth, are reviewed as well. Although the general health situation regarding iodine status has improved over years, iodine deficiency has not been eradicated. Further efforts to create safe and more efficient fortification procedures, focused follow‐up programs and healthy nutritional habits are still needed. Abstract : Relation between iodine cycling in nature and human intake/excretion.